The Role of Trust and Interaction in Tiktok Live and Shopee Live Live Live Shopping for Generation-Z Consumer Purchasing Interests - Nuzhuliya Mega Avifa; Elisa Tri Rahayu; Putri Firda Febrianti; Bilal Kautsar Setiabudi; Musleh, Musleh; Hawa Gazani (Penerbit Hellow Pustaka, 2025)
The development of digital technology has significantly changed the way people shop, especially Generation Z, who grew up in the digital age. One popular new trend is live shopping on TikTok Live and Shopee Live. This feature combines direct interaction between sellers and buyers with entertainment, making shopping more exciting and engaging. This study examined how trust and interaction influence Generation Z's interest in live shopping. The method used was interviews with several individuals who met the research criteria. The results showed that trust is a key factor, emerging from the host's credibility, the authenticity of the content, and the platform's reputation. Live interaction makes the shopping experience more personal, enjoyable, and reassuring. TikTok Live tends to encourage spontaneous purchases due to its entertainment concept, while Shopee Live supports planned purchases through detailed product information and attractive promotions.